Use of Biphasic Insulin Aspart 30 in Type 2 Diabetes Treatment: Expert Panel Recommendations - YAVUZ, DİLEK (GALENOS YAYINCILIK, 2018)
The goals of Type 2 diabetes treatment are to eliminate the hyperglycemia resulting from insulin insufficiency and/or insulin resistance, delay beta cell damage/depletion, and prevent other metabolic co-morbidities and complications. In the current treatment algorithms, lifestyle changes (medical nutrition therapy, physical exercise) and oral anti-diabetics are followed by insulin therapy, which is considered a replacement therapy for Type 2 diabetes. Pre-mixed insulin preparations, which are an option for patients with poor blood glucose level control under oral anti-diabetics treatment, have been developed to meet both basal and prandial insulin needs by simulating the physiological changes in insulin levels. The consensus on the necessity of individualizing insulin therapy requires physicians to have a detailed knowledge of the various uses of insulin. Therefore, this comprehensive consensus statement has been prepared by a panel of expert endocrinologists from different regions of Turkey to help physicians use biphasic insulin aspart 30 in suitable patients at the right time. In this statement, expert panel opinions on (a) Recommendations for the appropriate initiation, titration, and intensification of insulin treatment, and (b) The treatment algorithms in initiation, titration, and intensification of biphasic insulin aspart 30 treatment and special conditions specific to changing treatment regimen are presented.
Keywords: Biphasic insulin aspart 30; insulin intensification; premixed insulin; insulin analog; POSTPRANDIAL PLASMA-GLUCOSE; PANCREATIC-CANCER; GLYCEMIC CONTROL; CLINICAL ENDOCRINOLOGISTS; CARDIOVASCULAR EVENTS; AMERICAN ASSOCIATION; PREMIXED FORMULATION; INDEPENDENT RISK; HUMALOG MIX25; BLOOD-GLUCOSE